Intervenciones de enfermería en el soporte nutricional al paciente con cirugías neurológicas: revisión sistemática - García Yarlequé, Silvia Patricia (2025)
Introduction: The article addresses the nutritional interventions in neurological surgery patients focusing on nursing care for the recovery and dietary rehabilitation since in the postoperative period, the body undergoes great stress and increases the need for nutrients. Objective: To determine the nursing interventions that help improve nutritional support for the patient with neurological surgery. Methodology: It has a qualitative approach, transversal design, descriptive scope, it used the PRISMA method (Preferred Reporting Items for Systematic reviews and Meta-Analyses) to cover all mentioned knowledge in a transparent way in the areas of nursing, nutrition, enteral and parenteral supplementation. Results: The importance of the nurse’s role in the nutritional support of patients with neurological problems is highlighted who work in coordination with the medical and nutrition departments optimizing the available resources. The approach must be comprehensive considering the pathophysiology of the disease and carrying out an appropriate neurological assessment. A combination of personalized care, accurate evaluations, and well implemented strategies is key to provide an effective nutritional support, especially in neurological patients and in palliative care situations. Conclusion: Patients with neurological problems and even more who require surgical interventions are patients with a high risk who require nursing care to restore homeostasis and maintain nutritional status.